Harnessing Wearables and Digital Technologies to Decode the Cardiovascular Exposome - Geyner A. Gaona; Ali Asghar Kassamali; Nino Isakadze; Seth S. Martin (Methodist DeBakey Cardiovascular Journal)
The cardiovascular exposome encompasses the array of external and internal factors affecting cardiovascular health throughout life, inviting comprehensive monitoring and analysis to enhance prevention, diagnosis, and treatment strategies. Wearable and digital technologies have emerged as promising tools in this domain, offering longitudinal, real-time data on physiological parameters such as heart rate, heart rhythm, physical activity, and sleep patterns. This review explores the advancements in wearable sensor technology, the methodologies for data collection and analysis, and the integration of these technologies into clinical practice and research. Primary findings indicate significant improvements in device accuracy and functionality, facilitated by enhanced sensor technology, artificial intelligence, and data connectivity. These advancements enable precise monitoring, early detection of cardiovascular anomalies, and personalized healthcare interventions. Ultimately, wearables and digital health technologies have the potential to facilitate a deeper understanding of cardiovascular disease and behavior and bridge gaps in traditional healthcare models to help usher in more efficient, personalized, patient-centered care.